Ochratoxin A in cacao and derivatives. Preventive measures - C. Chire, Gabriela (2014)
A bibliographic review was made about the presence of ochratoxin A (OTA) in cocoa and cocoa products, its effects in human health, forms of detections, permitted legal levels, preventive and control measures, to make a extension of knowledge of each actor in the value chain (as farmer, sellers, manufacturers, exporters, the government, customers and so on) respect to this important topic and its relation with human health, as well as, stimulate to farmers and processors, use of code of practice.